2006
DOI: 10.1111/j.1468-3083.2006.01569.x
|View full text |Cite
|
Sign up to set email alerts
|

The detection of human herpesvirus‐8 DNA in plasma and peripheral blood mononuclear cells in adult patients with pityriasis rosea by polymerase chain reaction

Abstract: We conclude that PR is not associated with HHV-8 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 38 publications
0
23
0
2
Order By: Relevance
“…22 Viral DNA of HHV7 and HHV6 is reported to be present in the peripheral blood mononuclear cells and lesional and unaffected skin of the majority of individuals with acute PR. 23 With these scientific observations, PR can be considered as a viral disease caused by HHV7 and HHV6.…”
Section: Discussionmentioning
confidence: 99%
“…22 Viral DNA of HHV7 and HHV6 is reported to be present in the peripheral blood mononuclear cells and lesional and unaffected skin of the majority of individuals with acute PR. 23 With these scientific observations, PR can be considered as a viral disease caused by HHV7 and HHV6.…”
Section: Discussionmentioning
confidence: 99%
“…A study results reported by Chuh et alin order to investigate the association of PR with human herpesvirus-8 (HHV-8) infection. As the result of the study HHV-8 DNA was found to be negative in the peripheral blood mononuclear cells and plasma of acute and convalescent specimens of all patients, and negative in all skin scrapings (11).…”
Section: Discussionmentioning
confidence: 97%
“…As we know that pityriasis rosea has viral etiology so acyclovir has better response found in other study also. (5,6,7) Literature also says that Macrolide have anti-inflammatory effect. Apart from antibacterial effects, macrolides have effects on neutrophil function (Decreased oxidant production, apoptosis) and on the production of cytokines involved in the inflammation cascade (Decreased production of IL-1, IL- 6, IL-8, and TNF and increased production of IL-10 and, possibly, IL-4).…”
Section: Discussionmentioning
confidence: 99%